Play to Prepare: AR-Based Citizen Resilience - Jankó, Zsolt; Hölbling, Botond; Majdik, András László (Proceedings of the International ISCRAM Conference, 2026)
Our study presents a work-in-progress augmented reality (AR) application available on iOS and Android platforms that supports citizen preparedness through the simulation of various disaster scenarios. The system applies a serious game approach to provide an interactive, decision-centered learning experience for non-expert users. The aim of the application is to facilitate the acquisition of fundamental behavioral protocols, risk recognition skills, and appropriate response patterns within a safe and controlled environment. The proposed solution emphasizes experience-based learning embedded in the real environment, thereby increasing situational realism and the transferability of knowledge. The paper describes the technical architecture of the system and discusses in detail the challenges encountered during development. The system helps demonstrate that AR-based serious games can be an effective tool for strengthening citizen resilience and disaster preparedness.